PELATIHAN DIGITALISASI UMKM DAN PEMBUATAN AKUN E-COMMERCE: PELATIHAN DIGITALISASI UMKM DAN PEMBUATAN AKUN E-COMMERCE - Intan Pubiyanti; Aldi Dharma Putra; Budhi Setiawan; Muhammad Hafidh Hibatulloh; Niken Ayu Ambar Saputri; Wahyu Susilowati Sepsiana (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The purpose of training activities for digitizing Micro, Small and Medium Enterprises (MSMEs) and creating an E-Commerce account for the “Kelompok Wanita Tani” (KWT) is to help the KWT UKM community in solving the problems they face in an effort to develop a business, ranging from aspects of production and business management to especially in terms of marketing based on digitalization of MSMEs, which are expected to create economic independence and increase their business income. Specific targets in the UMKN digitalization training and KWT E-Commerce account creation are: 1) production programs; 2) Programs in Financial Management; and 3) Programs in marketing. Training on digitizing MSMEs and creating E-Commerce accounts was held on February 18 and March 02, 2021. This training and creation of E-Commerce accounts is aimed at KWT SMEs for Mandiri, Kenanga, and Cempaka businesses. E-Commerce made includes Shoppe, Facebook and Instagram accounts. It is hoped that with the training on digitizing MSMEs and creating E-Commerce accounts, people will form innovative entrepreneurs in the marketing process, independent and responsive to market demands so that they will make a positive contribution to society and the environment